Pro VB 2010 and the .NET 4 Platform - Troelsen, Andrew (Apress, 2012)
This book has been fully updated to provide coverage on the new features of the VB 2010 programming language, as well as the new features of the.NET 4 Platform. Here you will find information on the new Dynamic Language Runtime (DLR), the Task Parallel Library (TPL), Parallel LINQ (PLINQ), the ADO.NET Entity Framework (EF), and several “minor” (but very useful) updates, such as named arguments, optional parameters, the Lazy(Of T) class type, and so on.